Philosophical understanding of urban culture in an interdisciplinary context - Manassova, M.M.; Klishina, M.V. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The authors set themselves the goal of characterizing the culture and spiritual life of the city within the framework of an interdisciplinary approach. The article substantiates an interdisciplinary approach to the study of urban culture, since the complex ambiguous nature of city culture cannot be fully described and studied from the standpoint of any monodisciplinary approach. However, both cultural, semiotic and environmental factors are important in the study of certain aspects of the material and spiritual urban culture. The authors emphasize that the environmental approach is one of the most sought-after methodological approaches to analysis. Thus, urban architecture as the most important component of the city’s material culture, which differs in fundamental features in various historical eras, represented by various architectural styles (antique, architectural modernism, minimalism, etc.) and involves joint actions by designers, philosophers, architects, as well as civil engineers, financiers, representatives of local authorities and, most importantly, members of the public. The article provides an analysis of domestic and foreign studies of urban culture, shows the transformation of assessments of the city, urban spiritual life, urban culture. “Urban culture” is characterized as an artificially created environment for people to exist and realize themselves. The study examines the vectors of development of the culture of a modern city.
Keywords: chronotopy of the city; cultural capital; mission of culture; cross-cultural communications; cultural industries; modern city; creativity; contemporary urban culture; spiritual life of the city; urban culture; city